Texas microfungi: a new species of Corynesporopsis (Xylariales) associated with the trifoliate orange - Delgado, Gregorio; Koukol, Ondřej; Colbert, William (Phytotaxa, 2023)
Corynesporopsis ponciri sp. nov. is described from dead twigs, branches, and thorns still attached to trees of Poncirus trifoliata, the trifoliate orange, in Texas, U.S.A. The fungus is characterized by black, punctiform at first, later caespitose and hairy colonies forming large superficial patches covering almost entirely the surface of colonized parts of the host, unbranched conidiophores, solitary or fasciculate and arising from substomatal, compact stromata in loose to dense fascicles and bearing monotretic, mostly determinate, rarely percurrent conidiogenous cells. Conidia are ellipsoidal or fusiform to naviculiform, smooth or verruculose, brown, often with the apical cell light brown, euseptate, with 2, rarely 1 or 3 septa, usually with an associated dark band and forming short, unbranched, acropetal chains of up to four conidia. Multilocus phylogenetic analyses suggested that C. ponciri belongs within the Xylariales and forms a strongly supported monophyletic lineage sister to members of Vamsapriya in Vamsapriyaceae. Corynesporopsis is revealed as polyphyletic based on this and the other two species with available molecular data, C. iberica and C. acaciae. The newly described fungus is compared with morphologically similar species of Corynesporopsis and Heteroconium having 1- or 2-septate conidia and phylogenetic affinities of these polyphyletic anamorphic genera are discussed. The mode and successful colonization of dead parts of the host with conidiophores arising from substomatal stromata suggest that C. ponciri may have a putative endophytic stage and it is capable of switching to a saprobic lifestyle upon senescence or death of the host.